Anorexia nervosa and family therapy in a Chinese context - Ma, Joyce Lai-chong (Chinese University Press, 2011)
Over a ten-year period, Professor Ma carried out cross-disciplinary research in Hong Kong focused on the effectiveness of structural family therapy for Chinese patients suffering from anorexia nervosa. She found that though the Chinese patients received the same diagnosis as their Western counterparts, their experiences throughout the stages of the disease differed significantly due to interpersonal contexts and subjective cultural factors. The present collection synthesizes this clinical experience into a culturally specific, socially relevant, and clinically useful family treatment model for patients.